Factors impacting on the choice of entrepreneurship as a career by Barbadian youth : a preliminary assessment - Small, Joseann (2002)
Seeks to ascertain the career aspirations of Barbadians between the ages of 14-35 years. Identifies the factors associated with the desire to become an entrepreneur.